Persistent slip observed in TiZrNbHfTa: A body-centered high-entropy cubic alloy. (15th July 2021) - Tanaka, Masaki; Okajo, Shinji; Yamasaki, Shigeto; Morikawa, Tatsuya
Abstract: Slip properties of TiZrNbHfTa were evaluated to obtain ψ–χ relationships, where χ is defined as the angle between the maximum shear stress plane and ( 1 ¯ 01 ) . ψ is defined as the angle between the apparent slip plane and ( 1 ¯ 01 ) . Bending tests were conducted with micrometer-sized cantilevers fabricated from a single grain with a focused ion beam. Slip bands appear to be straight on a micrometer length-scale, as for Fe–Si alloys, which suggests a persistent slip. However, the ψ–χ relationship indicated that ψ is nearly the same as χ, suggesting that there is no persistent slip. Detailed observations with an atomic force microscope confirm that cross-slipping is so frequent at a sub-micrometer length-scale that the slip bands appear to be straight and the maximum shear stress plane is observed on a micrometer length-scale. Here, TiZrNbHfTa shows abnormally frequent cross-slipping, which is a novel characteristic of high-entropy body-centered cubic alloys. Graphical abstract: Image, graphical abstract